Association Between Serum Thyroid Measurements and Hyperhomocysteinemia in Euthyroid Subjects: A Retrospective Cross-Sectional Study - Zou J; Wang Y (Diabetes, Metabolic Syndrome and Obesity, 2023)
Jiayun Zou,1 Yuhan Wang2 1Department of Thyroid Surgery, The First Hospital of China Medical University, Shenyang, Liaoning, People’s Republic of China; 2Department of Cardiovascular, The First Hospital of China Medical University, Shenyang, Liaoning, People’s Republic of ChinaCorrespondence: Yuhan Wang, Department of Thyroid Surgery, The First Hospital of China Medical University, No. 155, Nanjing North Street, Heping District, Shenyang, Liaoning, People’s Republic of China, Email yhwang08@126.comObjective: The objective of this study was to investigate the association between serum thyroid measurements and homocysteine (HCy) in euthyroid participants.Methods: This retrospective study was based on Hospital Information Systems. After excluding participants with thyroid dysfunction and those who had recently taken medications that affected serum HCy, 775 participants were enrolled. We compared the serum thyroid function measurements of patients with or without hyperhomocysteinemia (HHCy) and analyzed the effect of thyroid indicators on HHCy prevalence and HCy levels. Multivariate regression analysis was utilized to analyze the association of thyroid-stimulating hormone (TSH) and thyroid peroxidase (TPOAb) with HCy.Results: The serum TSH level (2.10 ± 1.06 mIU/L) of HHCy patients (n = 98) was significantly higher than controls (n = 677) (1.65 ± 0.90 mIU/L) (p < 0.05), as was the positive rate of TPOAb (19.4% vs 10.0%, p < 0.05). The serum HCy levels in subjects with TSH within the highest quartile were significantly higher than those in the lowest quartile (13.49 ± 7.78 vs 9.81 ± 3.59 μmol/L, p < 0.05). HCy was also significantly higher in TPOAb-positive patients than in negative subjects (14.06 ± 8.89 vs 11.48 ± 5.47 μmol/L, p < 0.05). Among the TSH quartiles, the prevalence of HHCy showed a similar significant upward trend to that described above. The prevalence of HHCy was also significantly higher in TPOAb-positive patients. The results of multivariate regression analysis suggested that both TSH elevation and TPOAb positivity were independent risk factors for HCy elevation and HHCy prevalence. However, we found no definitive association between linear increases in TPOAb titers and HCy concentrations or HHCy prevalence.Conclusion: Patients with HHCy had significantly higher TSH levels and positive rates of TPOAb. Elevated TSH and positive TPOAb levels were independent risk factors for elevated HCy concentrations and HHCy risk.Keywords: thyroid stimulating hormone, thyroid peroxidase antibody, hyperhomocysteinemia, retrospective study